EFEKTIFITAS PEMBERIAN PROBIOTIK, PREBIOTIK, DAN SINBIOTIK MELALUI PAKAN UNTUK PRODUKSI SINTASAN BENIH UDANG WINDU (Penaeus monodon) - satriani, Gloria ika; Kartina, Kartina; Asna, Asna (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2024)
Tiger prawns produced in traditional ponds in North Kalimantan, especially Tarakan City, are a superior commodity susceptible to attack by pathogens. One way to prevent disease is to add probiotics. Probiotics are live microbes that help the host maintain microbial balance in the digestive tract. Prebiotics, conversely, are foods that cannot be digested by the host body but have a positive effect by selectively stimulating the growth of some bacteria in the intestine, such as Lactobacillus sp, thereby improving the host's health. To support the survival and growth of beneficial bacteria in the digestive tract, synbiotics combine probiotics and prebiotics in a balanced manner. It is hoped that administering probiotics and prebiotics will allow the growth of probiotic bacteria and other beneficial bacteria to improve the host's health. The research was carried out using a Completely Randomized Design (CRD) consisting of 5 feed treatments with three replications, namely 1: negative control consisting of commercial feed Feng Li-0, 2: positive control consisting of commercial feed Feng Li-0 added with a physiological solution and egg white, 3: prebiotic honey added to commercial feed Feng Li-0 along with physiological solution and egg white, 4: probiotic Lacto-B added to commercial feed Feng Li-0 along with physiological solution and egg white, and treatment 5: synbiotic honey and bacteria (Lacto-B) added to commercial feed Feng Li-0 along with physiological solution and egg white. This research aims to determine how effective prebiotics, probiotics and synbiotics are in producing black tiger shrimp juvenile survival. In this research, the synbiotic treatment showed the highest average survival value, final weight, and length in black tiger shrimp (Penaeus monodon) juvenile.